Pemikiran Filsafat Pendidikan Rekonstruksionisme: Implikasi terhadap Pendidikan Karakter dan Pendidikan Moral - Gema Adhari; Siti Nurhidayatul Marati; Herlini Puspika Sari (SURAU : Journal of Islamic Education, 2024)
Reconstructionism is a school of educational philosophy that aims to reshape society through radical educational reform. Rooted in a critique of progressivism, it emerged as a response to social and economic stagnation and the desire to make education an agent of social change. Its leading figures, such as George Counts and Harold Rugg, inspired by the thought of John Dewey and Theodore Brameld, advocate for an education that is able to deal with global challenges, including moral, social and environmental issues. Reconstructionism argues that education is not only responsible for shaping individuals, but also plays a role in building a just and equal society. The principles of this school emphasize the important role of education in dealing with the global crisis, as well as the need for a relevant curriculum to foster students' character and morals. This school places teachers as agents of change who play an important role in guiding students to face the challenges of the times, as well as designing a curriculum that prioritizes social interests. Thus, reconstructionism emphasizes the importance of education in saving civilization through the formation of character, morality, and a new, more humanist culture. AbstrakRekonstruksionisme adalah aliran filsafat pendidikan yang bertujuan untuk membentuk kembali tatanan masyarakat melalui reformasi pendidikan yang radikal. Berakar dari kritik terhadap progresivisme, aliran ini muncul sebagai respons terhadap stagnasi sosial dan ekonomi serta keinginan untuk menjadikan pendidikan sebagai agen perubahan sosial. Tokoh utama aliran ini, seperti George Counts dan Harold Rugg, terinspirasi oleh pemikiran John Dewey dan Theodore Brameld, mengadvokasi pendidikan yang mampu menghadapi tantangan global, termasuk isu moral, sosial, dan lingkungan. Rekonstruksionisme berpendapat bahwa pendidikan tidak hanya bertanggung jawab untuk membentuk individu, tetapi jquga berperan dalam membangun masyarakat yang adil dan setara. Prinsip-prinsip aliran ini menekankan pentingnya peran pendidikan dalam menghadapi krisis global, serta perlunya kurikulum yang relevan untuk membina karakter dan moral siswa. Aliran ini menempatkan guru sebagai agen perubahan yang berperan penting dalam membimbing siswa menghadapi tantangan zaman, serta merancang kurikulum yang mengutamakan kepentingan sosial. Dengan demikian, rekonstruksionisme menekankan pentingnya pendidikan dalam menyelamatkan peradaban melalui pembentukan karakter, moralitas, dan budaya baru yang lebih humanis